PENGARUH GAMBAR IKLAN PERINGATAN MEROKOK PADA BUNGKUS ROKOK TERHADAP SIKAP BERHENTI MEROKOK BAGI PELANGGAN MEREK SAMPOERNA A MILD DI DESA KEPENUHAN BARAT MULYA - -, Herman (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
ABSTRACT This study aims to determine the respondents to the ad images on cigarette packs warning against the attitude of quitting smoking for customer brand Sampoerna A Mild West Fullness In the village Mulya. Based on Survey Data From 5 Shop In The Fullness District of Rokan Hulu in October 2015 as many as 106 people. Samples will be taken by 51 respondents. Furthermore, the method of sampling used acidental Sampling. Analysis of the data using a questionnaire with Likert scale measurement and testing using simple linear regression. Based on the results of the study that the influence of advertising images of smoking warning (X) amounted to 0,746 this means that there is positive and if the level or effected by one unit then the attitude of quitting smoking increased by 0,746 units. The influence of advertising images of smoking warning against the attitude of quitting from the value t count by 13,765 to 0.00 significantly smaller than 0.05 this means that the influence attitudes towards smoking cessation quit smoking is a significant gesture. Suggested ad image warning smoke should be encouraged frequency through private television (cable TV) in the village Fullness of West Mulya Central City specifically or Rokan Hulu is often watched by adult smokers, so the image ads warning smoke are more effective and can improve attitudes to quit smoking adult smokers. Keywords: Image advertising and customer attitudes.1 2